Isolated Enteric Cyst in the Neck - Amit Mahore; Raghvendra Ramdasi; Palak Popat; Shilpa Sankhe; Vishakha Tikeykar (Case Reports in Otolaryngology)
We report an extremely rare case of isolated enteric cyst in the neck region which was diagnosed on the histopathological examination. It was suspected to be duplication cyst on radiology. We have also evaluated the differential diagnosis and management issues.